De la marginalisation au dénigrement des discours féministes - Blais, Mélissa ("J'haïs les féministes" : Le 6 décembre 1989 et ses suites, 2009)
Keywords: amériques; antiféminisme; approches et analyses; communication; cours; discipline; fem1000; histoire; médias; premier cycle; québec; régions géographiques; sciences humaines

J'haïs les féministes: le 6 décembre 1989 et ses suites - Blais, Mélissa (Les éditions du remue-ménage, 2009)
«J’haïs les féministes», la déclaration de Marc Lépine au moment d’ouvrir le feu sur des étudiantes de l’école Polytechnique le 6 décembre 1989, a suscité une vive controverse, répercutée dans les médias dès le lendemain de la tragédie. Pourtant, 20 ans plus tard, cet événement qui a profondément marqué la mémoire collective est toujours absent des livres d’histoire du Québec. S’inscrivant à même le travail de mémoire, cet ouvrage, à travers une étude minutieuse des médias (en particulier, des quotidiens La Presse, Le Devoir et The Globe and Mail), retrace l’évolution des réactions à la tuerie. Mélissa Blais s’intéresse aux multiples explications du geste de Marc Lépine, et défend les analyses et discours féministes, nés dans l’urgence, puis violemment discrédités ou détournés, malgré les intentions clairement exprimées par le tueur. Elle examine également les principales commémorations, notamment celles entourant le 10e anniversaire, et consacre un chapitre au film Polytechnique sorti en 2009. «J’haïs les féministes»: le 6 décembre 1989 et ses suites éclaire les débats entre féminisme et antiféminisme encore présents derrière cette tragédie
Keywords: amériques; antiféminisme; approches et analyses; chantier antiféminisme RéQEF; communication; cours; discipline; fem1000; histoire; médias; premier cycle; québec; régions géographiques; sciences humaines; thématiques; violences

Before tomorrow Le jour avant le lendemain - Cousineau, Marie-Hélène; Ivalu, Madeline (Alliance Vivafilm, 2009)
D'après le roman de Jørn Riel. Deux familles inuites se rencontrent pour une fête estivale. La nourriture est abondante et l'avenir semble prometteur, mais Ningiuq, une vieille femme forte et sage, ne cesse de s'inquiéter. Elle voit son monde comme fragile et le traverse avec un sentiment d'effroi omniprésent. Ningiuq part avec son petit-fils vers une île isolée, où ils sèchent les prises et les stockent pour l'hiver. La tâche est terminée et la saison chaude touche à sa fin, car ils attendent en vain que les autres viennent les chercher.
Keywords: 1800-1899; amériques; canada; cinéma; communication; cours; discipline; fem3200; histoire et politique; inuits; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; thématiques

In a queer time and place: Transgender bodies, subcultural lives - Halberstam, Jack (J.) (New York University Press, 2005)
In a Queer Time and Place opens with a probing analysis of the life and death of Brandon Teena, a young transgender man who was brutally murdered in small-town Nebraska. After looking at mainstream representations of the transgender body as exhibited in the media frenzy surrounding this highly visible case and the Oscar-winning film based on Brandon's story, Boys Don’t Cry, Halberstam turns her attention to the cultural and artistic production of queers themselves. Halberstam examines the “transgender gaze,” as rendered in small art-house films like By Hook or By Crook, as well as figurations of ambiguous embodiment in the art of Del LaGrace Volcano, Jenny Saville, Eva Hesse, Shirin Neshat, and others. Halberstam then exposes the influence of lesbian drag king cultures upon hetero-male comic films, such as Austin Powers and The Full Monty, and, finally, points to dyke subcultures as one site for the development of queer counterpublics and queer temporalities. Considering the sudden visibility of the transgender body in the early twenty-first century against the backdrop of changing conceptions of space and time, In a Queer Time and Place is the first full-length study of transgender representations in art, fiction, film, video, and music. This pioneering book offers both a jumping off point for future analysis of transgenderism and an important new way to understand cultural constructions of time and place.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; cinéma; communication; cours; discipline; fem1000; har4600; identités LGBTQIA2+; lit4700; personnes trans*; premier cycle; périodes historiques; queer; régions géographiques; thématiques; transféminisme; états-unis; études culturelles

No future: Queer theory and the death drive - Edelman, Lee (Duke University Press., 2004)
In this searing polemic, Lee Edelman outlines a radically uncompromising new ethics of queer theory. His main target is the all-pervasive figure of the child, which he reads as the linchpin of our universal politics of “reproductive futurism.” Edelman argues that the child, understood as innocence in need of protection, represents the possibility of the future against which the queer is positioned as the embodiment of a relentlessly narcissistic, antisocial, and future-negating drive. He boldly insists that the efficacy of queerness lies in its very willingness to embrace this refusal of the social and political order. In No Future, Edelman urges queers to abandon the stance of accommodation and accede to their status as figures for the force of a negativity that he links with irony, jouissance, and, ultimately, the death drive itself. Closely engaging with literary texts, Edelman makes a compelling case for imagining Scrooge without Tiny Tim and Silas Marner without little Eppie. Looking to Alfred Hitchcock’s films, he embraces two of the director’s most notorious creations: the sadistic Leonard of North by Northwest, who steps on the hand that holds the couple precariously above the abyss, and the terrifying title figures of The Birds, with their predilection for children. Edelman enlarges the reach of contemporary psychoanalytic theory as he brings it to bear not only on works of literature and film but also on such current political flashpoints as gay marriage and gay parenting. Throwing down the theoretical gauntlet, No Future reimagines queerness with a passion certain to spark an equally impassioned debate among its readers
Keywords: amériques; approches et analyses; cinéma; communication; cours; cycles supérieurs; discipline; fem1000; fem7000; lit2815; lit3220; lit3495; premier cycle; psychanalyse; queer; régions géographiques; sciences humaines; thématiques; violences; états-unis; études culturelles

Hedwig and the angry inch - Mitchell, John Cameron (Warner Brothers, 2001)
A gender-queer punk-rock singer from East Berlin tours the U.S. with her band as she tells her life story and follows the former lover/band-mate who stole her songs.
http://media2.criterionpic.com/display/114?t=XRNL2110
Keywords: allemagne; amériques; approches et analyses; cinéma; communication; cours; discipline; europe; fem3200; genre; identités LGBTQIA2+; premier cycle; queer; régions géographiques; thématiques; états-unis